Study of adolescent health behavior towards non-communicable disease risk factors in Special Region of Yogyakarta - Luthfi Nur Rochman Sudarko; Sitti Nur Djannah; Lina Handayani; M. Syamsu Hidayat; Intan Wahyuni Tukiyo (Universitas Ahmad Dahlan, 2023)
Backgrounds: Non-Communicable Diseases (NCDs) are still one of the causes of high incidence and death rates in people of various age groups, especially adolescents with poor lifestyles and health behaviors due to a lack of awareness to prevent NCDs from an early age. This study aimed to analyze adolescents health behavior of adolescents aged 15-24 years toward risk factors for non-communicable diseases based on the RISKESDAS results of the Special Region of Yogyakarta. Methods: This research is a quantitative descriptive study using secondary data to analyze the health behavior of adolescents aged 15-24 towards risk factors for non-communicable disease behavior based on data collected from RISKESDAS data for the Special Region of Yogyakarta in 2007, 2013, and 2018. Data analysis was carried out descriptively for each risk factor and presented as a percentage chart. Results: The research shows that the risk factors for smoking every day and occasionally have decreased from 2007 to 2018. There has been an increase in the awareness of consuming fruits and vegetables. Meanwhile, there was an increase in alcohol consumption in 2018 and a decrease in doing sufficient physical activity for one week in adolescents aged 15-24 years in the Special Region of Yogyakarta. Conclusion: It can be concluded that risk factors for health behavior related to non-communicable diseases in adolescents are still caused by a lack of physical activity and the large number of adolescents who consume alcohol.